Ethnocentrism and Purchase Intention of Foreign and Domestic Products: A Systematic Review to a Conceptual Framework - Kartikasari, Dwi; Almunawar, Mohammad Nabil; Anshari, Muhammad; Sumardi, Wardah Haki Haji (Universitas Islam Negeri Sunan Kudus, 2024)
Globalization prompts manufacturers of both international and local products to devise marketing strategies to stimulate the purchase intentions. This research aims to review the underlying theories applied to explain ethnocentrism and purchase intention of foreign and domestic products, as well as the independent and mediating variables, the relationship direction (sign) of major variables to the dependent variables, and the conceptual framework development based on this systematic review. We source the Scopus database and conclude with 31 articles under consideration. We apply a qualitative approach and find that the major theories include the social identity theory and the theory of planned behavior. The central independent variables are consumer ethnocentrism (CET), attitude (ATT), perceived behavior control (PBC), and subjective norms (SUB). The main mediating variable is ATT. We also discover support for relationships between CET, ATT, PBC, SUB, and purchase intentions of domestic or foreign products. We propose a conceptual framework consisting of the major variables. The study implies that CET is more important than ATT to drive the purchase intention of domestic products but not that of foreign products. The study is limited in the context of the countries, product types, and constructs that future research should address.